The Effectiveness of Abdominal Stretching Exercises Using the Cat Stretch Exercise Technique Toward Menstrual Pain Among Young Women in Indonesia - Permaini, Titi; Fauziah, Siti Nisa (STIKep PPNI Jawa Barat, 2024)
Aims: The high prevalence of dysmenorrhea more than 30% indicates the need to address this issue among adolescents. Severe pain during menstruation will affect psychosocial and physical changes. Some factors contribute to dysmenorrhea. Several non-pharmacological ways are already applied but the effect is still changing. One of the current innovations is abdominal stretching using the cat method. However, the effectiveness of this method is still unknown. This study explores the effectiveness of abdominal stretching exercises among adolescent girls in Indonesia. Method: The study design uses a quasi-experimental approach with one group pre-test and post-test design. Convenience sampling was applied in this study. This study was conducted in one of the senior high schools in Indonesia in one month in 2022. Instruments were used VAS (Visual Analog Scale). Data was analyzed using a Paired Sample T-Test. Results: The total sample is 20 adolescent girls. There is a significant difference in the menstrual pain scale before and after stretching abdominal exercises with p = 0.000. Conclusion: Abdominal exercise stretching can be applied in providing comprehensive nursing care to adolescents who experience dysmenorrhea. A structured operational procedure must be taken into consideration when applying this intervention.